Compatibility and efficacy of vaporised hydrogen peroxide technology to decontaminate reusable personal protective equipment. Issue 1 (31st December 2022) - Rondinone, Daniela; Karitonas, Tautvydas; Allegra, Enrico
Abstract: This study aimed to evaluate VHP as a decontamination method for decontaminating reusable PAPR; determine if PAPR is compatible with VHP; and determine how long it takes for hydrogen peroxide to off-gas for the mask to be safe for reuse. Off-gassing validation study which consisted of doing three VHP decontamination processes followed by three Off-Gassing Tests to confirm the efficacy of the VHP cycle and time required for the VHP concentration to reach 0 ppm. HALT, which consisted of exposing the PAPR to 50 VHP decontamination cycles followed by a Visual Appearance Test to determine if the VHP process impacted the PAPR material's visual properties. The results from this study show that VHP is an effective and repeatable process for decontaminating PAPR, and the Off-Gassing Test shows that with the appropriate off-gassing set up, it is possible to off-gas one PAPR within 8 hours of completing the decontamination cycle. The results from the Visual Appearance Test show that exposing a PAPR to 50 decontamination cycles does not present significant changes in the PAPR material's colour, opacity, or overall visual appearance.